Mass production : products from Phaidon design classics volume two. (London : Phaidon, 2006)
This book looks at the period after the Second World War, which was characterized by rapid reconstruction and modernization that spread throughout society and across social classes. Germany, Italy and Japan, thanks to financial assistance from the USA, increased the production and worldwide export of products that had already reached high standards in both design and technology. More and more manufacturers became conscious of the importance of good design, not only for products aimed at an elite cognoscenti but also those destined for the booming middle class. With so many products available and competition so high, designers were expected to make things easier to manufacture, use and distribute as well as more beautiful. Post-war housing was brighter and more spacious than ever before. Kitchens were fitted with modern appliances that made household chores easier and more enjoyable. Charles and Ray Eames, Jean Prouve, Arne Jacobsen and Alvar Aalto, among others, were commissioned to design furniture and appliances for the middle class home. Televisions, radios and telephones became commonplace and were designed to look stylish, to be left on display rather than being hidden away. Transport was becoming more sophisticated, with scooters, small cars and airplanes allowing people increased mobility. The universal desire for speed prompted designers to create some of the greatest sports cars ever.